Asymmetric construction of dihydrobenzofuran-2, 5-dione derivatives via desymmetrization of p-quinols with azlactones. Issue 1 (4th December 2018) - Xie, Lihua; Dong, Shunxi; Zhang, Qian; Feng, Xiaoming; Liu, Xiaohua
Abstract : 3-Amino-benzofuran-2, 5-diones containing a chiral amino acid residue were achieved throughBG-1 ·HBPh4 catalyzed enantioselective Michael addition/lactonization cascade reaction of p -quinols with azlactones. Abstract : The desymmetrization of p -quinols through a chiral bisguanidinium hemisalt catalyzed enantioselective Michael addition/lactonization cascade reaction with azlactones was reported. 3-Amino-benzofuran-2, 5-diones containing a chiral amino acid residue were achieved with up to 99% ee and >19 : 1 dr. An exploration of the structure of the catalyst bisguanidinium was undertaken, revealing a bifunctional catalytic model.